2014
DOI: 10.18632/oncotarget.1782
|View full text |Cite
|
Sign up to set email alerts
|

Immune regulation by low doses of the DNA methyltransferase inhibitor 5-azacitidine in common human epithelial cancers

Abstract: Epigenetic therapy is emerging as a potential therapy for solid tumors. To investigate its mechanism of action, we performed integrative expression and methylation analysis of 63 cancer cell lines (breast, colorectal, and ovarian) after treatment with the DNA methyltransferase inhibitor 5-azacitidine (AZA). Gene Set Enrichment Analysis demonstrated significant enrichment for immunomodulatory pathways in all three cancers (14.4-31.3%) including interferon signaling, antigen processing and presentation, and cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
359
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 390 publications
(399 citation statements)
references
References 33 publications
(48 reference statements)
29
359
1
5
Order By: Relevance
“…Of the cancers investigated to date, this effect is most pronounced in ovarian cancer cells (16). Treatment of ovarian cancer cells with the DNA methyltransferase inhibitor DAC (17) results in expression of cancer-testis antigens and MHC class I, increasing cancer cell recognition by CD8 þ T cells (18).…”
Section: Introductionmentioning
confidence: 99%
“…Of the cancers investigated to date, this effect is most pronounced in ovarian cancer cells (16). Treatment of ovarian cancer cells with the DNA methyltransferase inhibitor DAC (17) results in expression of cancer-testis antigens and MHC class I, increasing cancer cell recognition by CD8 þ T cells (18).…”
Section: Introductionmentioning
confidence: 99%
“…This results in gene silencing and has been associated with cancer development through the inactivation of tumor suppressor genes (10)(11)(12)(13)(14)(15)(16). Unlike DNA sequence alterations, epigenetic modifications, such as DNA methylation, are dynamic and reversible with proven therapeutic implications (17)(18)(19). Furthermore, this method of deregulating functional pathways is more straightforward and therefore Global methylation and promoter-specific methylation of the P16, SOCS-1, E-cadherin, P73 and SHP-1 genes and their expression in patients with multiple myeloma during active disease and remission more likely to be effective than generating mutations or chromosomal aberrations (17).…”
Section: Introductionmentioning
confidence: 99%
“…1 Current data has also shown that epigenetic therapies, including the DNA-methylation inhibitors 5-Azacytidine (Aza) and 5-Aza-2 0 -deoxycytidine (5-Aza-dC) (Decitabine), boost immune signaling of tumor cells. 2,3 Therefore, cancer treatments combining inhibition of DNA methylation with blockage of immune checkpoint proteins are a promising new therapeutic direction. Two recent publications shed light on the basic molecular and cellular efficacy regarding the above therapies, 3,4 where one common link implicates the innate immune system.…”
Section: Introductionmentioning
confidence: 99%